THE CONCEPT OF CHILD IN THE PERSPECTIVE OF THE QUR’AN (THEMATIC INTERPRETATION STUDY) - Abd Halim Nasution (UIN Sumatera Utara Medan, 2020)
The revival of Islamic religion has formed a new atmosphere for the condition or fate of the children of Arabs. Islam forbids the killing of children through the prohibition of Allah, among others, contained in QS. Al-Isra/17: 31. Besides prohibits killing children, featuring the provisions of Islamic law that shows how important attention to and even how to look after children with a loving since before and after birth. The Qur’anic view of children globally formulated in the principle: